Impact of Shifting Cultivation on Litter Accumulation and Properties of Jhum Soils of North East India - Sapu Changkija and Samarendra Hazarika, Henry Saplalrinliana, Dwipendra Thakuria (Journal of the Indian Society of Soil Science, 2017)
This study assessed whether the slash-burn practice (jhum) induced disturbance on the above-ground biological inputs (plant biomass and forest floor litters, FFLs) had any influence on the soil processes in terms of soil enzyme activities. The jhum cycles of 5, 10 and 15 years from Mizoram and 5, 10 and 20 years from Nagaland were considered. Litter (adjacent fallow phase/secondary forest) and soil samples (burnt and unburnt cropping phases) were collected from three slopes (summit, shoulder and backslope) from each site and were analyzed for soil physicochemical and biochemical properties. Accumulation of FFLs increased significantly with the increasing length of fallow phase and accumulation dynamics showed an increasing trend in the order January > April > August > November. Values of bulk density (BD), pH, electrical conductivity (EC), avail-P and avail-K in soils under burnt sites were found higher relative to their values in unburnt sites and the reverse trend was true in case of soil organic carbon (SOC) and avail-N. Except BD, values of these soil properties were significantly higher in the longer fallow phase compared to that in shorter fallow phase (P